Are Sink Drainage Systems a Reservoir for Hospital-Acquired Gammaproteobacteria Colonization and Infection? A Systematic Review. (8th December 2020) - Volling, Cheryl; Ahangari, Narges; Bartoszko, Jessica J; Coleman, Brenda L; Garcia-Jeldes, Felipe; Jamal, Alainna J; Johnstone, Jennie; Kandel, Christopher; Kohler, Philipp; Maltezou, Helena C; Maze dit Mieusement, Lorraine; McKenzie, Nneka; et al.
Abstract: Increasing rates of antimicrobial-resistant organisms have focused attention on sink drainage systems as reservoirs for hospital-acquired Gammaproteobacteria colonization and infection. We aimed to assess the quality of evidence for transmission from this reservoir. We searched 8 databases and identified 52 studies implicating sink drainage systems in acute care hospitals as a reservoir for Gammaproteobacterial colonization/infection. We used a causality tool to summarize the quality of evidence. Included studies provided evidence of co-occurrence of contaminated sink drainage systems and colonization/infection, temporal sequencing compatible with sink drainage reservoirs, some steps in potential causal pathways, and relatedness between bacteria from sink drainage systems and patients. Some studies provided convincing evidence of reduced risk of organism acquisition following interventions. No single study provided convincing evidence across all causality domains, and the attributable fraction of infections related to sink drainage systems remains unknown. These results may help to guide conduct and reporting in future studies.